Robust Control Strategy for Pneumatic Drive System via Enhanced Nonlinear PID Controller - Sy Najib Sy Salim; M.F. Rahmat; A. A. M. Faudzi; Z. H. Ismail; N.H. Sunar; Shamsul Anuar Samsudin (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This paper presents the pneumatic positioning system controlled by Enhanced Nonlinear PID (NPID) controller. The characteristic of rate variation of the nonlinear gain that are readily available in NPID controller is utilized to improve the performance of the controller. A Self-regulation Nonlinear Function (SNF) is used to reprocess the error signals with the purpose of continuously generating the values for the rate variation. Subsequently, the controller has successfully been implemented on dynamically changing loads and pressures. The comparison with the other available method such as. NPID and conventional PID are performed and evaluated.  The effectiveness of this method with Dead Zone Compensator (DZC) has also been successfully demonstrated and proven through simulations and experimental studies.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6853